Kontektualisasi Pemikiran Politik Jean Jacques Rousseau di Indonesia - sukri, mhd alfahjri (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The research aims to analyze the contextualization of Jean Jacques Rousseau's political thought in Indonesia, including state of nature, social contracts, common will, freedom, and democracy. This study used a qualitative method to describe the results of the analysis. Data was obtained through books, journals, scientific articles and others. The result of research on state of nature is that before Indonesia existed there were already states in the form of kingdoms. As for the social contract established in Indonesia through Pancasila in a complicated way due to agreements and conflicts from several groups. But in the end Pancasila was able to unite the Indonesian nation to this day. Regarding the general will and freedom, in Indonesia, it is regulated in Pancasila and the 1945 Constitution of the Republic of Indonesia with various existing problems such as the abuse of general will and freedom that occurred during the Soekarno Guided Democracy and the Suharto Era. As for democracy, Rousseau views direct democracy as the best, while Indonesia is more familiar with representative democracy based on deliberation